Association between modern contraceptive use and child mortality in India: A calendar data analysis of the National Family Health Survey (2015-16). (August 2020) - Shukla, Ankita; Kumar, Abhishek; Mozumdar, Arupendra; Aruldas, Kumudha; Acharya, Rajib; Ram, F.; Saggurti, Niranjan
Abstract: Background: Influence of contraceptive use on increased gap between successive births and attributed reduced risk of child deaths is well documented in developing countries. However, there is scarcity of evidence on direct contribution of contraceptive use on child survival especially in Indian context. Methods: Using information given in the reproductive calendar history of the National Family Health Survey of India conducted in 2015–16, this study examines the effect of modern contraceptive use on childhood mortality – infant mortality rate (IMR) and under-five mortality rate (U5MR). Bivariate analysis and cox proportional hazard model is applied in the study. Results: Finding reveals that use of reversible contraceptives prior to birth resulted in low childhood mortality rates. IMR is 35 per 1000 live births among births with preceding use of modern reversible contraceptives as compared to 44 per 1000 live births among births with no use. Similarly, U5MR is 41 per 1000 live births as compared to 61 per 1000 live births among births with preceding use of contraceptive and no use respectively. The use of reversible modern contraceptives prior to birth is protective against child mortality even among births with preceding birth interval of less than 24 months. Conclusions: This study provides evidence of dual benefit of contraceptive use. Such information is important for promoting evidence-based advocacy to expand use of family planning services. This will help the country to achieve Sustainable Development Goal 3.2 which calls for end of preventable deaths during childhood. Highlights: First paper providing evidence of direct effect of modern contraceptive use on child mortality in India. Contraceptive use increases birth intervals, and births with large preceding birth intervals have higher chances of survival. Use of modern contraceptive prior to birth reduces risk of child mortality even in the absence of large birth intervals.